2003
DOI: 10.1242/jeb.00670
|View full text |Cite
|
Sign up to set email alerts
|

The effect of elevated intraocular oxygen on organelle degradation in the embryonic chicken lens

Abstract: SUMMARY In the vertebrate lens, nuclei and other cytoplasmic organelles are degraded in fiber cells situated in the center of the tissue. This is believed to ensure the transparency of the tissue. The mechanism that triggers this process is unknown. We hypothesized that standing gradients of oxygen generated within the tissue may serve as a spatial cue for organelle degradation. To examine this possibility, we incubated fertilized chicken eggs under hyperoxic (50% O2) or normoxic (21% O2)conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
(21 reference statements)
0
27
0
Order By: Relevance
“…These studies demonstrated that TNF-related molecules and their signalling components are expressed in the developing lens and therefore support the suggestion that TNFrelated signalling is potentially involved in regulating organelle loss in lens fibre cells and/or lens fibre cell differentiation. The results therefore suggest that organelle loss could be a process activated by TNFamediated cell signalling cascades, although the involvement of a passive process (such as a reduction in oxygen tension at a specific point within the lens fibre cell mass) cannot be ruled out [62].…”
Section: Overview Of Factors Involved In Lens Fibre Cell Differentiatmentioning
confidence: 82%
“…These studies demonstrated that TNF-related molecules and their signalling components are expressed in the developing lens and therefore support the suggestion that TNFrelated signalling is potentially involved in regulating organelle loss in lens fibre cells and/or lens fibre cell differentiation. The results therefore suggest that organelle loss could be a process activated by TNFamediated cell signalling cascades, although the involvement of a passive process (such as a reduction in oxygen tension at a specific point within the lens fibre cell mass) cannot be ruled out [62].…”
Section: Overview Of Factors Involved In Lens Fibre Cell Differentiatmentioning
confidence: 82%
“…These regions are diagrammed in Figure 1. The elimination of organelles from the FC region of the chicken lens begins at E12 and a transparent organelle-free zone (OFZ) is apparent by E15 (Bassnett and McNulty 2003; Costello et al 2013; Basu et al 2014b). The E13 stage of embryonic chicken lens development (E13) was chosen because this represents an early stage of OFZ formation when molecules required for removal of organelles would be expected to be up-regulated in the fiber cell zones.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, an increase in D signifies that organelle degradation is delayed (32). Organelle degradation commences in the mouse lens during the late stages of embryonic development, and by P2 (the age examined here) the OFZ is a well defined region in the center of the tissue.…”
Section: Figmentioning
confidence: 87%